(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
Triphala is a customary Ayurvedic course of action made from three Indian domestic developed common items: Terminalia chebula, Phyllanthus emblica, and Terminalia belerica. It is a tridoshic rasayana that equalizations and rejuvenates the three sacrosanct components that regulate human life. Triphala is affluent in cancer anticipation operators, antibacterial, anti-viral, and anti-cancer properties, and is known to cure cataract and treat Secured Secure Need Clutter (Makes a difference). It is a polyherbal definition with a one of a kind component of movement, profitable for all three doshas (vata, pitta, and kapha) and contains compounds such as gallic destructive, chebulagic destructive, and chebulinic destructive. Triphala’s tall Vitamin C substance and linoleic oil make it a tonic. It has different antioxidant, anti-inflammatory, antipyretic, torment diminishing, antibacterial, antimutagenic, wound recovering, anti-cariogenic, antistress, adaptogenic, anti-diabetic, and hypoglycaemic properties.